1999
DOI: 10.1007/bf01314958
|View full text |Cite
|
Sign up to set email alerts
|

Identification and localization of calcium-dependent protease II inNeurospora crassa andUromyces appendiculatus

Abstract: Summary. The existence of Ca2+-dependent protease II in crude extracts of Neurospora crassa and Uromyces appendiculatus was demonstrated by immunoblotting using specific antibodies. In both extracts two immunoreacting bands were observed. The molecular mass of the major band in N. crassa corresponded to 37 kDa, while that in U. appendiculatus was 43 kDa, similar to that previously reported for Allomyces arbuscula. Immunofluorescence of the enzyme was predominantly localized in the apical regions of germlings a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
(24 reference statements)
1
4
0
Order By: Relevance
“…The apical localization of CDP II, as shown in Fig. 2H, essentially confirmed our previous finding reported earlier [25]. The colocalization of the spectrin-like protein and CDP II in the N. crassa hyphal apices (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The apical localization of CDP II, as shown in Fig. 2H, essentially confirmed our previous finding reported earlier [25]. The colocalization of the spectrin-like protein and CDP II in the N. crassa hyphal apices (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…We have reported the presence of two calcium-dependent proteases (CDPs I and II) in the apical region of Allomyces, an aquatic fungus, and shown that their presence or absence is related to growth [4, [20][21][22][23][24]. An immunoanalogue of CDP II was also discovered and shown to be exclusively localized in the apical regions of the hyphae of an ascomycete fungus, Neurospora crassa, and a phytopathogenic basidiomycete, Uromyces appendiculatus [25]. Therefore, this colocalization of cytoskeletal proteins and CDP might have some functional significance.…”
mentioning
confidence: 99%
“…present during vegetative growth phase, but absent in the cells from the phase of reproductive differentiation (Ojha and Turian, 1985;Huber and Ojha, 1994). Immuno-labelling of the protein in the hyphae has shown that it is predominantly localized in growing hyphal tip region, not only in chytridiomycete, Allomyces but also in ascomycete, Neurospora crassa and basidiomycete, Uromyces appendiculatus (Huber and Ojha, 1994;Barja et al, 1999). The two enzymes differ in their ionic charge and relative molecular weight.…”
Section: Introductionmentioning
confidence: 96%
“…As the control, two samples (containing 12.5 µg soluble proteins each) were incubated in the reaction mixture without CDP II or Ca 2+ . The digested proteins in the samples were separated by SDS-PAGE and processed for western blotting as described elsewhere Barja et al, 1999).…”
Section: In Vitro Proteolysis Of Tubulins In Cell-free Extractmentioning
confidence: 99%
“…Indirect immunofluorescence microscopic studies of the spatial distribution of CDP II showed it was predominantly localized in the growing hyphal tips of A. arbuscula and in fungi as divergent as ascomycete, N. crassa and basidiomycete, Uromyces appendiculatus (Huber and Ojha, 1994;Barja et al, 1999). Cytoskeletal proteins, particularly the actins and tubulins, have also been shown to be abundantly present in the growing hyphal tips (Raudaskoski et al, 1991;Barja et al, 1991;Huber and Ojha, 1994).…”
mentioning
confidence: 99%